A taxonomic study on the genus Zethus Fabricius from Hong Kong, with proposal of a new synonym (Hymenoptera: Vespidae: Eumeninae) - Yeh, Wen-Chi; Barthélémy, Christophe (Zootaxa, 2023)
We review three leaf-cutter wasp species of the genus Zethus Fabricius, 1804 occurring in Hong Kong. Zethus malayanus Gusenleitner, 2010, syn. nov. is proposed as a junior synonym of Z. bakeri Giordani Soika, 1995; we clarify the status of Zethus dolosus Bingham, 1897 formerly reported from Hong Kong and add Z. angulatus Nguyen & Carpenter, 2016 as new to Hong Kong. We provide descriptions and high-resolution images for the three species, including male genitalia of Z. angulatus and Z. bakeri.